Studying Poems in Basic Education - Tureta, Nuciala Mognato; Cunha, Carla Moreira da; Castro, Mayelli Caldas de (The ESPecialist, 2025)
This article presents a teaching sequence practice on the textual genre “Poetry”. The teaching practice was conducted and applied with elementary and high school students, aiming to foster the understanding of Intertextuality in order to enhance critical thinking, stimulate creative writing, and promote reflection on the social contexts of the students involved. The applied methodology about the teaching sequence followed what was proposed by Dolz, Noverraz, and Schneuwly (2004) concerning the logical progression of activities. This study is theoretically based on Koch and Elias (2024) and Koch (2012, 2022), considering what the authors state about intertextuality; in addition to Mazzi (2011), who addresses what literary intertextuality is concerned, as a linguistic and discursive characteristic; Rouxel (2013) helps us to elucidate the interpretation of literary texts and their form of reception; and Teixeira (2011) who portrays a linguistic analysis and its contribution to the interpretation of texts. The interaction between texts is highlighted as fundamental for creating multifaceted and semiotic meanings, emphasizing the importance of contextual analysis and intertextual relationships in text interpretation. As a result, creative and engaging productions emerged from the reading circles and perceptive analysis of the poems "José" by Drummond and "Drummundana" by Alice Ruiz.